UJI AKTIVITAS ANTIDIABETES FRAKSI ETIL ASETAT DAUN PEPAYA (Carica papaya L.)TERHADAP TIKUS JANTAN WISTAR (Rattus norvegicus) - Neswita, Elfia; Naldi, Jefri; Kinanti, Dara; Nasution, Halimah Raina; Pramudita, Rufina; Nurasni (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Diabetes mellitus is a serious chronic disease that occurs when the pancreas does not produce sufficient insulin or when the body is unable to effectively utilize the insulin produced. Papaya leaves (Carica papaya L.) have been reported to possess potential antidiabetic properties. The novelty of this study lies in evaluating the antidiabetic activity of the ethyl acetate fraction of papaya leaves in male Wistar rats. This study aimed to determine the antidiabetic activity of the ethyl acetate fraction of papaya leaves in alloxan-induced male Wistar rats. Papaya leaf simplicia powder was extracted using the maceration method with 70% ethanol as the solvent. The concentrated extract was subsequently fractionated using ethanol–water, n-hexane, and ethyl acetate. Antidiabetic activity was evaluated using alloxan induction at a dose of 150 mg/kg body weight. Blood glucose levels were measured before alloxan induction to determine baseline values, two days after induction to confirm hyperglycemia, and every seven days for 14 days of treatment to assess changes in glucose levels. Phytochemical screening revealed that the ethyl acetate fraction contained alkaloids, flavonoids, and saponins. The results showed that the ethyl acetate fraction at a dose of 300 mg/kg body weight exhibited the highest antidiabetic activity, with a 64% reduction in blood glucose levels, slightly higher than the positive control, which showed a 63% reduction. In conclusion, the ethyl acetate fraction of papaya leaves at a dose of 300 mg/kg body weight demonstrates promising antidiabetic potential, likely attributable to its bioactive compounds.